PENGARUH HYPNOBIRTHING TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA TRIMESTER KETIGA DALAM MENGHADAPI PERSALINAN - Qurrata Ayun, Sofa; Camelia, Dina; Hidayati, Nurul (LPPM STIKES HUSADA JOMBANG, 2024)
Hypno-birthing is a technique of autohypnosis (self-hypnosis), which is a natural effort to instill positive intentions/suggestions into the soul/subconscious mind to reduce anxiety levels during labor and delivery preparation. Hypnobirthing aims to enable mothers to give birth comfortably and relieve the pain of childbirth without the help of any anesthetic. The aim of the study was to determine the effect of hypnobirthing on the anxiety level of primigravida TM III mothers in facing delivery at the Kwanyar Health Center. The population of all trimester III primigravida mothers in facing labor was 54 respondents with a sample of 48 respondents, the research location was at the Kyanyar Health Center, Bangkalan. The design of this study used a statistical test with the type of pre-experimental research with a pre-test and post-test approach. The sample collection technique used simple random sampling. The results of the study obtained an asym sign of 0.000, which means less than 0.05, meaning that there is an effect of hypnobirthing on the anxiety level of third-trimester primigravida mothers. . In the Wilcoxon statistical test, there is an output value in the form of ties, namely the similarity of events before and after treatment. In this study, there were FIES values ​​of 48 respondents who experienced changes before and after hypnobirthing on the anxiety level of primigravida mothers in the third trimester. It is recommended that the respondent's family be motivated to know and obtain information about hypnobirthing on the mother's anxiety level. Primigravida TM III in facing labor.